INTERRELATION OF LOGISTICAL AND MARKETING ACTIVITIES OF COMPANY - Курсенко, Юлия; Воловик, Елена (SWorldJournal, 2021)
Marketing and logistics are two key functions of any company. The way these structures interacts and influence each other within a good management system may result in cost reduction and main processes optimization. This article deeply analyzes marketing